MONOPOLI PERUSAHAAN RITEAL MODREND - Basir Basir Basir; Renny Rahmalia (Universitas Islam Negeri sultan syarif kasim Riau, 2021)
AbstractThe Indonesian retail industry is a strategic industry for Indonesia's economic development. In a claim, the Association of Indonesian Retailers (Aprindo), which has so far represented the interests of modern retailers, stated that the retail sector is the second sector that absorbs the largest workforce in Indonesia, with the ability to absorb 18.9 million people, under the agricultural sector which reached 41.8 million people. The presence of modern retail business actors has given its own color to the development of the Indonesian retail industry. In a short period of time several modern retail business actors with extraordinary capital capabilities carried out their activities in Indonesia. Dominia's position in Law Number 5 of 1999 Prohibition of Monopolistic Practices and Unfair Business Competition based on article 1 paragraph (4) and article 25 paragraph (1-2), it can be seen that the existence of modern retail has basically carried out monopolistic practices in certain areas. certain areas as required by Article 1 paragraph (4). Modern retail business actors can be said to have carried out monopolistic practices in certain areas by using their financial strength, ability to supply or sell certain goods or services. In general, modern retail has fulfilled these elements, namely finance, supply and sales, and the ability to adjust supply by business actors. Keywords: Monopoly, company, Riteal Modrend Abstrak Industri ritel Indonesia, merupakan industri yang strategis bagi perkembangan ekonomi Indonesia. Dalam sebuah klaimnya, asosiasi perusahaan ritel Indonesia (Aprindo), yang selama ini banyak mewakili kepentingan peritel modern menyatakan bahwa sektor ritel merupakan sektor kedua yang menyerap tenaga kerja terbesar di Indonesia, dengan kemampuan menyerap sebesar 18,9 juta orang, di bawah sektor pertanian yang mencapai 41,8 juta orang. Kehadiran para pelaku usaha ritel modern telah memberi warna tersendiri bagi perkembangan industri ritel Indonesia. Dalam jangka waktu yang singkat beberapa pelaku usaha ritel modern dengan kemampuan kapital yang luar biasa melakukan aktivitasnya di Indonesia. Mereka mewujudkannya dalam bentuk minimarket, supermarket bahkan hypermarket yang kini bertebaran di setiap kota besar Indonesia. Posisi dominia dalam Undang-Undang Nomor 5 tahun 1999 Larangan Praktek Monopoli dan Persaingan Usaha Tidak Sehat berdasarkan pasal 1 ayat (4) serta pasal 25 ayat (1-2), dapat dilihat keberadaan ritel modern ini pada dasarnya telah melakukan praktek monopoli di wilayah-wilayah tertentu sebagaimana yang disyaratkan oleh pasal 1 ayat (4).Pelaku usaha ritel modern bisa dikatakan telah melakukan praktek monopoli di wilayah-wilayah tertentu dengan mengunakan kekuatan keuangan, kemampuan pemasokan atau penjualan barang atau jasa tertentu. Pada umumnya ritel modern telah memenuhi unsure ini, keuangan, pemasokan dan penjualan, dan serta kemampuan penyesuian pasokan oleh pelaku usaha.Kata Kunci: Monopoli, Perusahaan, Riteal Modrend